Post-Apartheid Dance : Many Bodies Many Voices Many Stories. - Friedman, Sharon (Cambridge Scholars Pub., 2012)
The intention of this work is to present perspectives on post-apartheid dance in South Africa by South African authors. Beginning with an historical context for dance in SA, the book moves on to reflect the multiplicity of bodies, voices and stories suggested by the title. Given the diversity of conflicting realities experienced by artists in this country, contentious issues have deliberately been juxtaposed in an attempt to draw attention to the complexity of dancing on the ashes of aparthei ...